Dermatophytosis among Elementary School Students in Jatinangor West Java - Saskia, Dwi Bandang; Ramali, Lies Marlysa; Sadeli, Ramlan (Althea Medical Journal, 2016)
Background: Dermatophytosis is a common skin disease in tropical countries. In Indonesia, the incidence of dermatophytosis is quite high. Epidemiological studies showed that prevalence of dermatophytosis in children were higher than in adults. The aim of this study was to identify dermatophytosis cases among elementary school students in Jatinangor West Java.Methods: A descriptive study was carried out, involving 391 students aged 6â16 years from four elementary schools in Jatinangor West Java, who were selected by multi-stage sampling method. Six classes were chosen from each school. In every class, students were chosen to obtain the minimum number of samples. The inclusion criteria was elementary school students who were willing to participate in this study. The exclusion criteria were students who did not attend school at the time when the study wasperformed. The studyâs procedure consisted of six steps i.e. preparation, interview, screening, physical examination, specimen collection and microscopic examination. The collected data was processed by calculating the frequency and percentage.Results: The study discovered that out of 391 students, 197 suffered from non specific skin lesions. After confirmed by a dermatologist, three students were suspected to have dematophytosis lesion. From microscopical examinations by a microbiologist, two students had positive dermatophyte hyphae. The number of dermatophytosis cases in elementary school students, in Jatinangor was 0.5% (2/391).Conclusions: The incidence of dermatophytosis cases in this study is relatively low compared with other studies. Clinical features are tinea corporis. Both patients with positive dermatophyte hyphae are ten -year -old females. [AMJ.2016;3(2):165â9]DOI: 10.15850/amj.v3n2.808